আমলার মন - বন্দ্যোপাধ্যায়, আলাপন (কলকাতা : দে'জ পাবলিশিং, 2016)
Articles on the history of bureaucracy in India.
Includes bibliographical references.
Donated By Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: Bureaucracy -- India -- History; Public administration